Mechanical Electrical Coupling Modeling and Fault Characteristic of the Main Driving System of the Annealing Kiln - Kangqu Zhou; Lei Lei; Xueming Wu; Wennan Xie; Zhiqun Kan (Jixie chuandong)
According to the fault characteristics of the Main Drive System of the Annealing Kiln（MDSAK）， the nonlinear factors such as the time-varying meshing stiffness of the gear and the time-varying stiffness of the bearing are considered synthetically， the mechanical electrical coupling dynamics model of the MDSAK including the driving motor， the gear driving system and the load system is established. The influences of bearing outer ring fault and gear tooth break fault on the dynamic characteristics and electrical characteristics of the MDSAK are analyzed. The results show that when the fault occurs， the fault feature is to take the fault feature frequency of the shaft and gear where the fault occurs as the modulation signal， which produces the phenomenon of amplitude modulation and frequency modulation for the side frequency near the dominant frequency of each component， and also modulates the electrical signal. When the fault occurs in the bearing outer ring， the fault feature is to take the fault feature frequency of the outer ring as the modulation signal， which dominates each component. The side frequency around the frequency produces the phenomenon of amplitude modulation and frequency modulation， at the same time， it also modulates the electrical signal. The research results lay a theoretical foundation for the health monitoring and early warning of the MDSAK.